Phlebotomine sand flies (Diptera, Psychodidae) from Pha Tong cave, Northern Thailand with a description of two new species and taxonomical thoughts about Phlebotomus stantoni. - Marie-Charlotte Renaux Torres; Coline Pellot; Puckavadee Somwang; Pathamet Khositharattanakool; Khamsing Vongphayloth; Fano José Randrianambinintsoa; Bruno Mathieu; Padet Siriyasatien; Frédérick Gay; Jérôme Depaquit (Public Library of Science (PLoS), 2023)
Background In South-East Asia, Thailand is the country with the highest number of human autochthonous cases of leishmaniases mostly due to Leishmania martiniquensis. Their transmission remains unresolved to date even though sand flies are known vectors of leishmaniases. As such, we focused a study on the sand fly fauna of a cave in Thailand to explore the biodiversity of potential Leishmania vectors. Main results We carried out an inventory in Pha Tong cave. We caught and identified 570 Phlebotomine sand flies (452 females and 118 males) and identified 14 species belonging to the genera Phlebotomus, Idiophlebotomus, Chinius, Sergentomyia and Grassomyia. Among these 14 species, two could not be related to known sand fly species. Herein, we propose the description of two new sand fly species, previously unknown to science. The first new species, Phlebotomus shadenae n. sp. is a sand fly of the subgenus Anaphlebotomus. It is morphologically close to Ph. stantoni, a species widely distributed throughout Southeast Asia. However, it differs by the length of the genital filaments in males or by the length of the ducts of the spermathecae in females as well as the high divergence of cytochrome b sequences. Additionally, we revised the systematics of the subgenus Anaphlebotomus and reinstated, by examination of its holotype, the validity of Ph. maynei, an Indian wrongly considered as a synonym of Ph. stantoni in the past. The second new species, Sergentomyia maiae n. sp., differs from a species in the same group, Se. barraudi, by an original cibarial double row of vertical teeth as well as by molecular data. Conclusions We propose the description of two new sand fly species for Science with morphological and molecular evidence. Ph. shadenae n. sp. was also found to be distributed in the south of Thailand and in Laos. Future studies need to determine whether these two species can play a role as vectors of Leishmania parasites, Trypanosomatids or Phlebovirus. Most of the species caught in the present study are strictly cavernicolous except Grassomyia sp. and a few Sergentomyia.